REGIONAL ASPECTS OF MODERN INTERNATIONAL RELATIONS IN THE CONDITIONS OF WORLD GLOBALIZATION - Гірман, А. П.; Криша, В. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The modern world is determined with political interest in both territories and spatial relations. The article is devoted to some topical issues which are relaten to regional and subregional subsystems connecting with new trends in modern international relations: globalization, regionalization and fragmentation.For a long period of time, the subordinate nature of the problem of regional and subregional subsystems did not raise doubts in the categories of bipolar interaction.  The situation became more complicated after the collapse of the bipolar structure of relations. Therefore, the question has arisen as to what might be the criteria for dividing the world space in the new conditions.It was discovered that regional international systems are very complex connections between existing social communities, the interaction of which has certain features of a systemic spatial organization.  It  leads to the fact that regional processes can influence or reformate global ones. Different elements of the regional subsystem or various combinations of actors at the regional level affect the global level in different ways.  They can maintain and strengthen the global order, contribute to its radical breakdown and overthrow or evolutionary transformation into a new quality. Therefore, the regional level of analysis allows us to study the problems of countries and international relations, differentiate space / territories in accordance with quantitative and qualitative criteria, since the concept of physical and political boundaries takes on some relativity in the real world.Regional integration issues are particularly relevant to Ukraine since it has a unique choice  of its direction – European (integration into the EU) or Eurasian (integration into the Customs Union). Given this, the scientific justification of this choice is of great importance.